Jobs and the Crisis - McKenzie, David; Robalino, David (World Bank, Washington, DC, 2012)
In response to the financial and economic crisis, many countries sought to stimulate labor demand, facilitate job search and preserve skills, and protect income. While little information is available about the impact of these interventions, there is some evidence that they involved a substantial number of people despite limited budgets. At the same time, there are concerns about the effectiveness of programs, particularly in low- and middle- income countries. The challenge now is to revise the policy mix to maximize the impact of the recovery on employment creation.